Use of E-Wallet in the Covid 19 Era As A Measure Of The Advancement Of Digital Industry Technology In Indonesia - Ahmad Rezeki; Rio Ariangga; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2021)
Growing technological developments have led to more and more innovations and breakthroughs as the ages and eras continue to evolve, as well as human relationships that are constantly connected to one another, but what if for us to make payments, storage, or future investments E-WALLET is a breakthrough We will take a lead in our daily lives, even in Indonesia's bank data, which recorded more than 5 billion transactions over a period of 2019 a year, which proves that technological growth such as E-WALLET will be a new business in the E-PAYMENT aspect or in the digital financial age that can compete in today's globalization.